Alternating the environmental benefits of Aegle-diesel blends used in compression ignition. (15th November 2019) - Rajak, Upendra; Nashine, Prerana; Verma, Tikendra Nath; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: AMME – diesel blends can be used in a diesel engine without modifications. Engine performance suffers slightly with AMME addition. Smoke and PM emission is reduced using AMME biodiesel compared to diesel. Reduction of CO2 emission with increase in load. Abstract: The steady state condition diesel engines used for commercial applications, transportation and industries have led to the crisis of petroleum based fuel. The harmful emissions produced by compression ignition engines. In the present study, the performance, combustion, and emissions of aegle methyl ester biodiesel-diesel blends in a single cylinder, four strokes, direct injection, diesel engine at different loads, at constant advanced injection timing and speed of 1500 rpm, were simulated using Diesel-RK software. In order to optimize the use of aegle methyl ester (AME) biodiesel in diesel engines, the B20 blend of AME biodiesel was investigated. Oxides of nitrogen (NOX ) emission by AME biodiesel blends were higher than diesel; however, smoke and particulate matter (PM) emissions were found to be lower. The cylinder pressure for AME20 was higher than diesel at full engine load. Results showed that AME20 biodiesel had around 3.72, 4.2, 3.52, 6.68, and 17.0% lower thermal efficiency, peak heat release rate, exhaust gas temperature, pressure rise rate and ignition delay, respectively and about 3.16, 1.4 and 8.5% higher specific fuel consumption, cylinder peak pressure and sauter mean diameter, respectively, as compared to the diesel fuel at full loads. PM and smoke emissions for AME20 biodiesel blend was reduced by 17.2 and 20.8% while the NOX was emission higher by 8.5% as compared to diesel. The blend ratio AME20 of biodiesel was found to be higher performing in delivering acceptable engine characteristics at a higher fuel injection pressure of 220 bar and full load conditions.